Contextual factors impact styles of play in the English Premier League - Gollan, S.; Bellenger, C.; Norton, K. (Journal of Sports Science & Medicine, 2020)
The aim of this study was to evaluate the influence of contextual factors on game styles in professional soccer. Interactions between styles and different playing venues, opposition quality, total match goals, and competing styles, were investigated using logistic regression and odds ratios. Game styles were characterised using the moments of play framework where three distinct styles have been identified: Style 1 - moderate strength in defence; Style 2 - dominance in transition, and Style 3 - strength in attacking phases of play. Results revealed that when playing at home against teams identified by Style 1, teams were more likely to play Style 2 (p < 0.05) or Style 3 (p < 0.001). Against top 10 opposition, teams were less likely to play Style 3 compared to either Style 1 (p < 0.001) or Style 2 (p < 0.001). Regardless of venue, teams were more likely to play Style 3 against bottom 10 sides compared to either Style 1 (p < 0.001) or Style 2 (p < 0.001), suggesting a hierarchical order between contextual factors. Competing game styles significantly impacted total match goals scored, whilst match results were also influenced by game style combinations. Overall, this study showed the significant effects of various contextual variables on game styles played by teams in the EPL. Key Points